COMITE D'ORGANISATION DU CONGRES/CONFERENCE COMMITTEE - Dupuis, Onil; Deslauriers, Pierre; Rivet-Panaccio, Colette; Cowan, Georges; Sessions, Vivian; Chaput, Gilles; Butticaz, Brigitte; Pepin, Therese L.; Savoie-Dansereau, Francine; Groen, Frances; Laroche, Lyne; Boyer, Diane; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF